SELVFED GENRESAMPLING ELLER REFLEKSIV SAMTIDSLITTERATUR? - FIKTIONALISERING AF SELV OG SAMTID I WEIHUIS SHANGHAI BABY - Munk, Anne Myrup (K&K - Kultur og Klasse, 2013)
SELF-SATISFIED GENRE-SAMPLING OR REFLECTIVE CONTEMPORARY LITERATURE | This article applies the concept of ‘fictionality’ to Chinese Weihui’s self-fashioning in relation to her international bestseller Shanghai Baby (1999). Shanghai Baby is a novel that plays on the author’s own biography yet at the same time many parts of the narrative are clearly fictionalized. The article argues that Weihui’s self-fashioning in the novel and in the media is part of an international tendency in contemporary literature, a tendency towards using fictionality as a means to reinstall literature and the book as a medium in the global media ontology. Fictionality is here understood not as generic, but as a rhetoric strategy that can be deployed in any kind of communication as an intentional mediation of reality. Shanghai Baby is in many ways a popular multimedia phenomenon that instantly made Weihui a celebrity and spawned a number of internet-based rip offs. But it is also an example of how to understand fictionality in contemporary culture in the context of a highly hybrid, mediatized and globalized age.